Achieving Zero Leakage, Ultralong Lifespan, and Intrinsic Opening Sensing in Microvalves Through Structural Superlubrication and Triboelectric Nanogenerator Technologies - An, Jie (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 Wiley‐VCH GmbH.